Relationships Among Goal Contents, Exercise Motivations, Physical Activity, and Aerobic Fitness in University Physical Education Courses. Issue 2 (April 2016) - Sibley, Benjamin A.; Bergman, Shawn M.
The current research examined the relationships among exercise goal contents, behavioral regulation, physical activity, and aerobic fitness within the context of eight-week university physical education courses. Participants were undergraduate students ( M age = 20.2 year, SD  = 2.3) enrolled in activity courses ( N  = 461) during the 2010 Fall semester. At pretest, participants completed a demographic survey, Behavioral Regulation in Exercise Questionnaire and the Goal Contents in Exercise Questionnaire. At eight-week posttest, participants completed the Physical Activity Questionnaire for Adults and the PACER aerobic fitness test. Relative intrinsic goal content was found to predict physical activity indirectly and aerobic fitness via behavioral regulation. Specific goal contents related to health management and skill development were found to predict physical activity and aerobic fitness via a fully mediated path through identified and intrinsic regulation. Results supported the efficacy of goal contents and self-determination theory in describing physical activity behavior and fitness. Examining specific types of goal contents and behavioral regulations revealed relationships that were masked by the utilization of omnibus scoring protocols.